Peningkatan Literasi Keuangan dalam Pengelolaan Keuangan Pribadi pada Pelajar MTS Swasta Al Fattah Desa Tunggilis Kecamatan Kalipucang Kabupaten Pangandaran - Retno Widya Ningrum; Irfan Achmad Musadat; Agung Pramayuda (Jurnal Bhakti Karya dan Inovatif, 2023)
Financial literacy is knowledge, ability, and intelligence that affect attitudes and behaviors in decision-making and financial management in the framework. Therefore, financial literacy is needed from an early age so that people are more aware of the role of money and can manage money wisely. In addition, the habit of saving is also expected to have a positive impact such as determining the priority scale of needs, appreciating value more, and being more independent and consistent in achieving MTS Swasta Al Fattah students are currently the alpha generation, so they need an approach that suits their character. The method used in this community service is a service learning approach. Service learning methodology is a learning approach that combines real experiences in society with academic learning. This methodology aims to provide a direct contribution through the teaching process so that the skills and knowledge of MTS Swasta Al Fattah students are achieved. Community service activities that have been carried out are as follows: The participants already know the function of money as a medium of exchange but have not been able to distinguish between needs and wants. In addition, shopping activities in traditional markets and mini-markets also provide an understanding that shopping in conventional markets requires communication between sellers and buyers ranging from asking about the availability of goods to bargaining prices, while in markets it does not require much communication because the goods are already displayed with the price.